2017
DOI: 10.1016/j.kint.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia induces targeted autophagic degradation of aquaporin-2 at the onset of nephrogenic diabetes insipidus

Abstract: Hypercalcemia can cause renal dysfunction such as nephrogenic diabetes insipidus (NDI), but the mechanisms underlying hypercalcemia-induced NDI are not well understood. To elucidate the early molecular changes responsible for this disorder, we employed mass spectrometry-based proteomic analysis of inner medullary collecting ducts (IMCD) isolated from parathyroid hormone-treated rats at onset of hypercalcemia-induced NDI. Forty-one proteins, including the water channel aquaporin-2, exhibited significant changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 74 publications
0
65
0
Order By: Relevance
“…In addition to increased knowledge of normal kidney physiology, more studies are also needed to advance understanding of renal pathophysiology. For example, two recent proteomicdriven studies revealed a prominent role for selective autophagy in the downregulation of specific proteins during development of nephrogenic diabetes insipidus due to electrolyte imbalance disorders [hypokalemia (84) and hypercalcemia (82)]. Another proof-of-concept study recently demonstrated an application of proteomic analysis in exploring the molecular pathophysiology in an animal model of chronic tubulointerstitial fibrosis (137).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increased knowledge of normal kidney physiology, more studies are also needed to advance understanding of renal pathophysiology. For example, two recent proteomicdriven studies revealed a prominent role for selective autophagy in the downregulation of specific proteins during development of nephrogenic diabetes insipidus due to electrolyte imbalance disorders [hypokalemia (84) and hypercalcemia (82)]. Another proof-of-concept study recently demonstrated an application of proteomic analysis in exploring the molecular pathophysiology in an animal model of chronic tubulointerstitial fibrosis (137).…”
Section: Discussionmentioning
confidence: 99%
“…Hypercalcemia can cause AKI directly through a variety of mechanisms: afferent arteriolar vasoconstriction, leading to decreased glomerular filtration rate 73 ; binding of calcium to the CaSR on the basolateral membrane of the thick ascending limb, resulting in down-regulation of the sodium-potassium-chloride cotransporter, leading to natriuresis and volume depletion 74 ; and nephrogenic diabetes insipidus, which occurs as a result of enhanced autophagic degradation of aquaporin-2 channels in the inner medullary collecting ducts. 75 In addition, hypercalcemia can cause hypercalciuria, nephrolithiasis, and nephrocalcinosis, which can cause both acute and chronic renal impairment.…”
Section: Hypercalcemia and Akimentioning
confidence: 99%
“…Therefore, although we do not provide direct in vivo data that CaSR activation contributes to vasopressin resistance and polyuria in dKO mice, indirect in vivo and direct ex vivo data strongly support this hypothesis. In line with this, recent data indicate that hypercalcemia‐induced hypercalciuria, by exposing cells to sustained elevated extracellular calcium, causes AQP2 autophagic degradation that is mediated by CaSR activation (66). Cell‐surface AQP2 abundance is crucial to the maintenance of body water homeostasis; however, it should be considered that dKO mice may also have a moderate defect in the generation of the cortical‐medullary gradient as a result of the down‐regulation of NKCC2 (20), which is also critical for the production of concentrated urine.…”
Section: Discussionmentioning
confidence: 65%